ChemInform Abstract: P(n‐Bu)3 Catalyzed Reactions of Salicyl N‐Thiophosphinyl Imines with Allenylphosphonates: Synthesis of Phosphono‐Chromans. Issue 47 (6th November 2014) - Rama Suresh, R.; Prasad Tulichala, R. N.; Kotikalapudi, Ramesh; Kumara Swamy, K. C.
Abstract Optimum reaction conditions are examined for the reaction of N‐thiophosphinyl imines (I) with allenylphosphonates (II) or (V).